Parasitology Research Founded as Zeitschrift für Parasitenkunde - Ryan, Una.; Walochnik, Julia; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The journal Parasitology Research is a broad readership, international, peer-reviewed journal publishing significant and original contributions on the latest developments in parasitology across a variety of disciplines, including biology, medicine, and veterinary medicine. Among many topics discussed are chemotherapy and control of parasitic disease, and the relationship of host and parasite. Publishes Reviews, Original Research, Brief Report and Correspondence. With international and highly qualified Board of Section Editors Topics: General, Biological, Medical and Veterinary Parasitology Protozoology, Helminthology, Entomology Morphology (incl. Pathomorphology, Ultrastructure) Biochemistry, Physiology (incl. Molecular Biology) Parasite-Host-Relationships (incl. Immunology, Host Specificity) Life History, Ecology, Epidemiology Diagnosis, Chemotherapy and Control of Parasitic Diseases If your research includes the description of new species or deals with very specific questions in systematics, taxonomy, and nomenclature, we encourage you to consider the journals Systematic Parasitology and Acta Parasitologica, as their expert editorial boards are more suitable to handle this research. Editorial Policies: Manuscripts submitted to Parasitology Research should adhere to rigorous scientific standards, including originality, clarity, and ethical conduct. We welcome submissions in categories: Reviews, Original Research, Brief Report and Correspondence. Only Reviews prepared by experts in the field will be considered for publication. The journal promotes open access and encourages the sharing of data and resources to foster collaboration and transparency in parasitology research.
Keywords: Medical microbiology; Microbiology; Immunology; Medical Microbiology; Microbiology; Immunology